LED array-based multi-angle light scattering for aspirating smoke detection and classification - Soocheol Kim; Hoesung Yang; Kwangsoo Cho; Kyuwon Han; Yusun Ahn; Jin Hwa Ryu; Kangbok Lee (Scientific Reports)
Abstract Although smoke detectors are actively being studied to reduce false fire alarms, they still face challenging issues such as complex and elaborate alignment, high cost, large size, and poor performance. In particular, most smoke detection systems based on Mie scattering, which rely on single-scattering measurements, may not perform effectively in real-world environments where multiple scattering occurs. We present an advanced smoke detection instrument for aspirating smoke detection and classification based on multiple scattering. Multi-angle light scattering with an LED array instead of angle-positioned PDs was measured, and the unique optical property ratios of fire and non-fire aerosols were calculated. The feasibility of smoke detection and classification was verified by evaluating the classification performance of 10 types of fire and non-fire aerosols using general supervised learning algorithms. The advanced smoke detection instrument features a simple design, making it cost-effective and compact. In addition to reducing false fire alarms, it is expected to contribute to choosing appropriate fire extinguishers based on fire class and advancing research of complex fire detection.